The Relationship between Pre-miR-3131 3-bp Insertion/Deletion Polymorphism and Susceptibility and Clinicopathological Characteristics of Patients with Breast Cancer - Azizi, Mahsa; Rahimi, Nahid; Bahari, Gholamreza; Hashemi, Seyed M.; Hashemi, Mohammad (MicroRNA, 2020)
Aims: This study aimed at examining the effect of 3-bp pre-miR-3131 insertion/deletion (ins/del) polymorphism on Breast Cancer (BC) risk. Objectives: Totally 403 women including 199 BC patients and 204 women who have no cancer were included in this case-control study. Genotyping of miR-3131 3-bp ins/del polymorphism was performed by mismatch PCR-RFLP method. Methods: The findings expressed that the pre-miR-3131 3-bp ins/del variant was not related to the risk of BC in all genetic tested models. While, the ins/del genotype was related to late onset BC (OR=2.53, 95%CI=1.27-4.84, p=0.008). Results: Pooled results from the meta-analysis indicated to that the pre-miR-3131 ins/del is related to with an increased risk of cancer in heterozygous (OR=1.26, 95%CI=1.06-1.51, p=0.01), dominant (OR=1.33, 95%CI=1.14-1.54, p=0.0002), and allele (OR=1.24, 95%CI=1.06-1.45, p=0.006) genetics models. Conclusion: It is concluded that, our findings did not support a relationship between pre-miR-3131 ins/del polymorphism and the risk of BC. While, this variant was significantly related to late onset BC. Combined results of this study with previous studies indicated that this polymorphism increased the risk of cancer. More studies in a study with larger population with variety of ethnicities are required to verify our findings.
Keywords: deletion